Integrating Deming and Six Sigma Principles in School Greenship Initiatives: A Narrative Inquiry Perspective - Sutikno Sutikno; R. Madhakomala (Dinasti International Journal of Education Management and Social Science, 2025)
This research examines how combining Deming's Plan-Do-Check-Act (PDCA) Cycle with Six Sigma's DMAIC (Define, Measure, Analyze, Improve, Control) principles can strengthen green initiatives in schools as part of sustainable education governance. Adopting a narrative inquiry design, the study captures the lived experiences of principals, teachers, and facility coordinators in executing environmentally responsible practices in accordance with the Greenship standards of the Green Building Council Indonesia (GBCI). Data were gathered through in-depth interviews and document analyses from selected environmentally oriented schools. The results indicate that integrating Deming and Six Sigma methodologies facilitates more systematic planning, monitoring, and evaluation of sustainability efforts, thereby enhancing environmental efficiency, resource optimization, and a culture of continuous improvement across the school community. The study underscores that the effectiveness of Greenship implementation relies not only on adherence to technical standards but also on collaborative leadership, active stakeholder participation, and reflective learning processes. Ultimately, this work contributes to the discourse on sustainable school management by proposing a practical model that connects quality improvement systems with environmental accountability in educational institutions.